Gender differences in symptom misattribution for coronary heart disease symptoms and intentions to seek health care. Issue 4 (20th April 2020) - Biddle, Caitlin; Fallavollita, James A.; Homish, Gregory G.; Giovino, Gary A.; Orom, Heather
ABSTRACT: Women are more likely to delay seeking care for coronary heart disease (CHD) symptoms than men. We tested whether this was because they are more likely to misattribute CHD symptoms. Data were collected in December 2016. Participants were 714 Amazon's Mechanical Turk (crowdsourcing marketplace) workers with US Internet Protocol (IP) addresses; 52% female (ages 35–77 years) made judgments about patients of their same gender described in vignettes. We used adjusted multivariable logistic, ordinal, and linear regression to test our hypotheses. Women had a higher odds of misattributing the symptoms of the target in the vignettes to non-cardiac causes than men (adjusted odds ratio [AOR] = 2.08, p < .001), despite having higher mean knowledge scores about CHD (4.49 vs. 4.03, p < .001) and rating their CHD risk as higher (25% more likely to get CHD vs. 19%, p = .025) than men. Women were also less likely than men to intend to seek care at an emergency department (b = −0.33, p = .024), and if they did intend to seek care, they were more likely to intend to wait to seek care (AOR = 2.37, p = .003). Symptom misattribution may partially account for women's lower likelihood of intending to seek care from an emergency department, which would be especially critical in emergency situations.